Public transport in Singapore and a financial analysis of premium bus services - Ong, Kevin Tiong Hock. (2008)
A good public transport system is an essential success factor in both developed and developing countries. Singapore, with its growing economic prosperity and affluence, has seen its vehicle population increase rapidly. The resulting traffic congestion on its roads is further compounded by the space constraints of land-scarce Singapore. This report studies how the government has attempted to make public transport more attractive than private car ownership : by keeping faires at a reasonable level, building a comprehensive road network and providing an alternative mode of transport in the form of the Mass Rapid Transit.